Availability of right femoral vein as a route for tunneled hemodialysis catheterization - Shindo M (Dove Medical Press, 2018)
Mitsutoshi Shindo,1 Hiroaki Takemae,2 Takafumi Kubo,2 Masatsugu Soeno,2 Tetsuo Ando,2 Yoshiyuki Morishita1 1Division of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, Saitama, Japan; 2Department of Dialysis and Transplant Surgery, Hidaka Hospital, Gunma, Japan Purpose: This study was performed to investigate the primary patency rate and catheter-related problems associated with use of the femoral vein as a route for tunneled hemodialysis catheterization compared with those of the right internal jugular vein as the first-choice route in patients undergoing maintenance hemodialysis. Patients and methods: Twenty-two patients underwent placement of indwelling tunneled hemodialysis catheters in the right internal jugular vein as the first option for maintenance hemodialysis, and 20 patients underwent placement in the right femoral vein as the second option. The primary patency rate of the catheters and catheter-related problems at 1, 3, 6, and 12 months after placement were investigated. Results: The 1-, 3-, 6-, and 12-month primary patency rates of the tunneled hemodialysis catheters in the right internal jugular vein were 95.5%, 95.5%, 81.3%, and 58.3%. The primary patency rates of the catheters in the right femoral vein were 95.0%, 89.5%, 86.7%, and 66.7%. There were no statistically significant differences in the primary patency rates at 1, 3, 6, and 12 months or in catheter-related problems between the right internal jugular vein and right femoral vein. Conclusion: The primary patency rate and catheter-related problems of indwelling tunneled hemodialysis catheters placed in the right femoral vein were not different from those in the right internal jugular vein in patients undergoing maintenance hemodialysis. These results suggest that the right femoral vein might be a useful option for placement of indwelling tunneled hemodialysis catheters in patients undergoing maintenance hemodialysis. Keywords: tunneled hemodialysis catheter, right femoral vein, primary patency rate, catheter-related problems